THE SIGNIFICANCE OF THE WORK “FIRDAVS UL-IQBAL” BY HISTORICIAN MUNIS AND OGAHII IN THE RESEARCH OF RELATIONS BETWEEN THE KHANATE OF KHIVA AND RUSSIA DURING THE PERIOD OF KHAN MUHAMMAD RAHIMKHAN I OF KHIVA (1806-1825) (TAMADDUN NURI JURNALI, 2025)
The article talks about the importance and necessity of the work “Firdavs ul-Iqbal” by historians Munis and Agakhi in studying the relations between the Khiva Khanate and Russia during the reign of Muhammad Rahimkhan I. Information is provided that the work is a primary source in the analysis and study of relations between the two countries, and that researchers can obtain important information from the work.